2013
DOI: 10.5812/aapm.14618
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between the Effects of Alfentanil, Fentanyl and Sufentanil on Hemodynamic Status During Rapid Sequence Intubation in the Emergency Department

Abstract: Background:Laryngoscopy and tracheal intubation lead to the alteration of hemodynamic parameters, including blood pressure and heart rate, in traumatic patients who sustain rapid sequence intubation (RSI). Various drugs such as fentanyl, alfentanil and sufentanil have been used to modify these hemodynamic responses.Objectives:The aim of the present study is to compare the effects of fentanyl, sufentanil and alfentanil in trauma patients who require RSI in the emergency department (ED).Patients and Methods:This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 19 publications
1
31
1
1
Order By: Relevance
“…There are several other trials of intubation with fentanyl or other similar opiates that compared it to no intervention or lidocaine; these studies found that opiates can attenuate the sympathomimetic response to intubation better than placebo or lidocaine (31)(32)(33)(34)(35). The only caveat to the use of fentanyl is to ensure an adequate dose is used.…”
Section: Resultsmentioning
confidence: 99%
“…There are several other trials of intubation with fentanyl or other similar opiates that compared it to no intervention or lidocaine; these studies found that opiates can attenuate the sympathomimetic response to intubation better than placebo or lidocaine (31)(32)(33)(34)(35). The only caveat to the use of fentanyl is to ensure an adequate dose is used.…”
Section: Resultsmentioning
confidence: 99%
“…Managing the respiratory status and level of tissue oxygenation is important in treating trauma patients in the emergency department and should be one of the first steps in patient evaluation. Urgent action should be taken to improve respiratory status, and taking care of the neck spine of trauma patients is essential before any diagnostic intervention (11, 12). …”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl and alfentanil minimize changes in heart rate and blood pressure during intubation of trauma patients. 73 In a prospective, randomized non-obstetric study of patients with baseline hypertension, fentanyl (with and without lidocaine) decreased but did not eliminate the hemodynamic response to laryngoscopy. 74 In a randomized trial of obstetric patients, fentanyl 1 lg/kg administered three minutes before induction of general anesthesia resulted in a stable hemodynamic profile during laryngoscopy, without affecting Apgar scores or blood gas analysis.…”
Section: Hemodynamic Considerationsmentioning
confidence: 99%